Freud’s concept of the unconscious: a philosophical ontology of human existence - Ta, Ha Van Thi (Griot : Revista de Filosofia, 2025)
This article explores the ontological dimension of Sigmund Freud’s psychoanalytic theory, focusing particularly on the concept of the unconscious and its foundational role in shaping human existence. While Freud did not claim to be a philosopher, his analysis of the human psyche led him to confront core philosophical questions regarding the nature of being. The study traces how Freud’s clinical method—originally developed to treat mental illness—evolved into a broader inquiry into the structure of the human personality through key concepts such as the Id, Ego, and Superego. By positioning the unconscious not merely as a psychological phenomenon but as a central element in the ontological structure of the human being, Freud inadvertently contributed to reconfiguring the philosophical understanding of the self. Drawing comparisons with classical and modern Western philosophical thought, the article demonstrates that Freud’s theory bridges psychology and philosophy, revealing human beings as complex, internally conflicted entities shaped by both instinctual drives and sociocultural norms. In doing so, Freud laid the groundwork for a philosophical anthropology in which the human subject is no longer understood solely through consciousness and reason, but as a dynamic intersection of unconscious forces and cultural formations.